2019
DOI: 10.1002/ece3.5170
|View full text |Cite
|
Sign up to set email alerts
|

A pre‐Miocene Irano‐Turanian cradle: Origin and diversification of the species‐rich monocot genus Gagea (Liliaceae)

Abstract: The Irano‐Turanian (IT) floristic region is considered an important center of origin for many taxa. However, there is a lack of studies dealing with typical IT genera that also occur in neighboring areas. The species‐rich monocot genus Gagea Salisb. shows a center of diversity in IT region and a distribution in adjacent regions, therefore representing a good study object to investigate spatial and temporal relationships among IT region and its neighboring areas (East Asia, Euro‐Siberia, Himalaya, and Mediterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
1
25
1
Order By: Relevance
“…alpina/ruthenica complex with disjunct populations in different mountains: from the Tian Shan in central Asia to the Caucasus, Balkans, European Alps and the Iberian Peninsula 41 , 42 . Similar results have been obtained in other steppe taxa originated in the Irano-Turanian Region 28 , 29 , 51 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…alpina/ruthenica complex with disjunct populations in different mountains: from the Tian Shan in central Asia to the Caucasus, Balkans, European Alps and the Iberian Peninsula 41 , 42 . Similar results have been obtained in other steppe taxa originated in the Irano-Turanian Region 28 , 29 , 51 .…”
Section: Discussionsupporting
confidence: 89%
“…Steppe flora and vegetation are present in the Mediterranean basin (comprised Western Europe) since the Paleogene and gained relevance throughout the Neogene, especially during the Miocene 10 , 20 . The geographical origin of the main steppe lineages that colonized the Mediterranean basin is Central and Western Asia 15 , 30 , 51 and this is also the case for Rhaponticoides (Fig. 4 ) because Turkey appears as the most probable ancestral area.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Tulips ( Tulipa L.) are famous ornamental and cut flowers due to their beautiful and colorful corolla [ 14 – 16 ]. Tulipa is a member of Liliaceae sensu APG IV [ 17 ], subfamily Lilioideae, tribe Tulipeae Kostel [ 18 , 19 ]; the tribe Tulipeae including Gagea Salisbury, Amana Honda, Erythronium L., and Tulipa [ 20 ] is sister to the tribe Lilieae [ 21 ]. The close relationship between Gagea and Tulipa , Amana , and Erythronium is generally accepted; however, the phylogenetic relationships among Tulipa , Amana , and Erythronium have remained controversial due to inconsistencies across studies and lack of strong support [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a member of the Liliacae family, with a wide geographic distribution and beautiful yellow flowers in early spring. Looking at the ribosome and chloroplast DNA of 116 species of the genus Gagea has shown that the group originated in southwestern Asia, where it began its diversification in the early Miocene 6 .…”
Section: The Twelve Blooms Of Christmasmentioning
confidence: 99%